Beyond a Doctorate of Musical Arts: Experiences of its impacts on professional life. Issue 3 (13th June 2018) - Draper, Paul; Harrison, Scott
Abstract : There is much dialogue in the academy about the role of doctoral studies in relation to employment, career trajectories and graduate outcomes. This project explores the experiences of Doctor of Musical Arts (DMA) graduates and students at the Queensland Conservatorium in Australia to reveal how the programme has impacted upon their professional activities, while also addressing assumptions promulgated through the literature on artistic practice and research education. The paper presents emergent themes and concludes by offering insights into artistic research in music more broadly.